Sistem Pemilihan Laptop Berdasarkan Kriteria Kebutuhan Dengan Metode Simple Multi Attribute Rating Technique (Smart) (Studi Kasus: Toko Laptop Guard Yogyakarta) - Herli Setiawan; Arita Witanti (Journal Of Information System And Artificial Intelligence, 2021)
In the process of buying laptops, it is found out that customers at Laptop Guard Store are often confused when to select the specification of the laptop they need. They sometimes take a long time to choose the most appropriate laptop for them. The Simple Multi-Attribute Rating Technique (SMART) method is a decision support system that can help them select a laptop. This method starts with determining criteria, assigning criteria weight, normalizing criteria weight, determining sub-criteria, assigning sub-criteria weight, determining utility values, calculating total values, ​​and drawing conclusions in the form of rankings or final recommendations. The criteria include college majors, brands, applications, processors, and prices. The results of this study will provide suggestions for laptop buyers to suit their needs for a laptop with a letter level of accuracy based on the needs calculation. The results of the accuracy testing of the system that have been made with calculations and is currently carried out by the company using 50 samples show an output of 100% relevant and 0% irrelevant. In this study, Asus laptops had the highest percentage of selection of 60%, Acer 34%, and Lenovo 6%. Keywords: laptop, decision support system, SMART.